The Dark Side of Collection Management: Deselecting Serials from a Research Library's Storage Facility Using WorldCat Collection Analysis - Ward, Suzanne M.; Aagard, Mary C. (Collection management, 2008)
To address the situation of its nearly full storage facility, the Purdue University Libraries developed guidelines for the deselection of very low-use serial titles and conducted a pilot project to identify material for withdrawal. The library school intern hired to conduct the pilot used WorldCat Collection Analysis to create subject lists of titles to be considered for withdrawal. These lists also contained value-added information about how many benchmark institutions owned and duplicated the local holdings of each title. Working with subject specialists, the intern developed criteria to guide a major serials deselection project. After the success of the internship in six subject areas, the libraries funded a longer-term position to complete the deselection project.